Participation of Financial Institutions in the Processes of Financial Stabilisation and Sustainable Development - Kosztowniak, Aneta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The aim of the article is to present the most important legal regulations in the field of ESG and their impact on the conditions of financial stability and the implementation processes of sustainable development in financial institutions.Research Design & Methods: The research methods focus on presenting and assessing changes in ESG and climate disclosure scores for institutions in the global economy and green asset ratio (GAR) indicators for EU/eurozone countries. Empirical data come from online reports and databases from the Working Group on Climate-related Financial Disclosure (TCFD), Financial Stability Board (FSB), European Board Authority (EBA) and European Insurance and Occupational Pensions Authority (EIOPA), and Sustainalytics. The main period of analysis covers the years 2022–2024.Findings: Data from the TCFD and FSB show that banks and insurance companies demonstrate the highest level of ESG disclosure, including in the area of strategy. Institutions from Europe, Asia-Pacific, and North America are leading the disclosure curve. Among EU/EEA countries, Slovakia, Iceland, and Luxembourg demonstrated the highest level of transformation activity in terms of the share of GAR in assets in 2023–2024.Implications / Recommendations: Financial institutions actively shape the conditions for financial stability and sustainable development because they are subject to legal regulations in these areas. Financial and economic outcomes depend on the efficiency of financial institutions’ management boards and the effectiveness of mitigating systemic risks (ESG, climate) in these areas. According to the Fit-for-55 report, financial institutions would incur the lowest costs under the baseline scenario.Contribution: The analysis fills a gap in the research on the role of financial institutions in the global economy, including in the EU/EEA, in shaping the conditions for financial stability when implementing ESG transformation processes revealed, among others, in reporting and changes to GAR indicators.